MODEL COMMUNITY LEARNING BERBASIS DISCOVERY UNTUK MENINGKATKAN SOFTSKILLS STOIKIOMETRI KIMIA PESERTA DIDIK SMA (Jurnal Inovasi Pendidikan Kimia, 2019)
Soft skills are things that become part of learning outcomes in the learning process. This is related to the provision of the lives of students in the future. The aim of the chemical stoichiometry learning process with discovery-based community learning models is to improve students' soft skills. This classroom action research was carried out in 3 cycles with 3 meetings each cycle. The research subjects were softskills for students of class X Science-6 Pekalongan 1 High School. The results of the study showed an increase in students' soft skills from 67% (less) in cycle 1 to 87% (good) in cycle 2. In cycle 3 it increased to 96% (very good), with very good indicators of success. This increase shows that discovery-based community learning models can improve students' soft skills. Other results indicate a change in enthusiasm, activity, and motivation to learn to be better.